2013
DOI: 10.1007/s00264-013-1798-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparing navigation-based in vivo knee kinematics pre- and postoperatively between a cruciate-retaining and a cruciate-substituting implant

Abstract: Purpose Individual physiological knee kinematics are highly variable in normal knees and are altered following cruciatesubstituting (PS) and cruciate-retaining (CR) total knee arthroplasty (TKA). We wanted to know whether knee kinematics are different choosing two different knee designs, CR and PS TKA, during surgery using computer navigation. Methods For this purpose, 60 consecutive TKA were randomised, receiving either CR (37 patients) or PS TKA (23 patients). All patients underwent computer navigation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
19
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 33 publications
(43 reference statements)
5
19
1
Order By: Relevance
“…[2] and Baier et al. [4] confirmed that the anterior instability during mid-flexion reported by Victor et al. [1], which is due to paradoxical anterior femoral translation of the medial condyle, is commonly seen in CR TKA.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…[2] and Baier et al. [4] confirmed that the anterior instability during mid-flexion reported by Victor et al. [1], which is due to paradoxical anterior femoral translation of the medial condyle, is commonly seen in CR TKA.…”
Section: Discussionsupporting
confidence: 89%
“…reported slight mid-flexion instability in CR compared with PS TKA [4], and Massin et al. detected paradoxical displacements in hyper congruent prostheses [5].…”
Section: Introductionmentioning
confidence: 94%
“…This motion sequence could, however, only be tracked when the anterior-cruciate ligament was intact [1]. Knee kinematics after TKA revealed a variety of movement patterns, including almost physiological sequences but also paradoxical forward slide of the femoral condyles during flexion [3,13,22]. Regardless of cruciate-retaining or cruciate-substituting implants, normal knee kinematics are rarely observed [13,31].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been conducted to investigate the kinematics of the knee after TKA . Early studies performed investigation of TKA kinematics using motion analysis system to quantify the 6DOF kinematics of the TKA knees and compared the data to normal knees .…”
mentioning
confidence: 99%